Perception Of Body Image And Health Control In Patients With Psoriasis: How It Is Related - Zajančkauskaitė-Staskevičienė, Loreta; Kužmarskytė, Miglė (Slauga. Mokslas ir praktika, 2022)
Psoriasis is a chronic, systemic, inflammatory skin disease that causes rashes on the skin of the body, scalp and nails. People with psoriasis face a variety of psychosocial difficulties due to their illness. The quality of life in psoriasis deteriorates due to the perceived stigmatization in society that a person affected by the disease may experience. Rashes, dandruff is often considered subjectively the worst aspect of the disease, as visible skin lesions change patients’ appearance and perception of body image. A person well-being and health-related behaviors are related to a person’s perception of their health locus of control. The aim of this study was to investigate the relationship between perceived stigmatization, body image perception, and health locus of control in psoriasis patients. Participants filled the Feelings of Stigmatization Questionnaire, Dresden Body Image Questionnaire (DBIQ-NL) and the Multidimensional Health Locus of Control Scale (MHLC). The study involved adults with psoriasis (n = 111). The results showed that men with psoriasis have a more positive perception of the body, have perception that others were responsible for their health. The degree of skin damage in patients is directly related to perceived stigmatization. For psoriasis sufferers, the belief that control over their health is beyond their control acts as a mediator between perceived stigma and body acceptance.